Rewired glycolysis by DTL accelerates oncometabolite L-lactate generation to promote breast cancer progression - Liu, Yuhao; Li, Jinting; Cao, Yiren; Lv, Mengzhu (Frontiers in Oncology, 2025)
Breast cancer (BC) has become the leading cause of global cancer incidence. Despite therapeutic advances, a critical unmet need persists for identifying novel therapeutic targets. Our integrated bioinformatics analysis identified DTL, a component of the Cullin-RING ligase (CRL) E3 ubiquitin ligase family, as significantly upregulated in BC tissues. This upregulation correlated with poor patient prognosis, cancer stemness, and metabolic reprogramming, which was driven by genetic alterations such as gene amplification and reduced promoter methylation. Functional studies demonstrated that DTL promoted breast cancer cell proliferation and migration in vitro through glycolysis remodeling. Mechanistically, DTL positively regulated key glycolytic enzymes (HK2, ENO1, PKM2, and LDHA) independently of its canonical ubiquitin ligase activity and directly interacted with LDHA. Notably, exogenous L-lactate directly enhanced BC tumor growth and metastasis. Collectively, our findings reveal a non-canonical mechanism whereby DTL drives glycolysis to generate the oncometabolite L-lactate, which directly sustains breast cancer malignancy independent of protein degradation. The strong association between DTL upregulation and adverse clinical outcomes, coupled with its multifaceted regulatory roles in tumor biology, highlighting its therapeutic potential as a novel target in BC.